Penggunan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar IPA Konsep Gaya Pada Siswa Kelas IV Kristen Patti: Indonesia - Wetamsair, Jenita; Talakua, Melvie; Wattimury, Ince (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the Problem Based Learning (PBL) model in improving students' learning outcomes in the science concept of force for fourth-grade students at SD Kristen Patti. The research employed Classroom Action Research (CAR) methodology with 19 students as the subjects. Data were collected through learning outcome tests and observation sheets on teacher and student activities during the learning process. The research procedure consisted of two cycles including planning, action implementation, observation, and reflection. The results showed that the application of the Problem Based Learning model could improve students' learning outcomes in the science concept of force. This is evidenced by the increasing average test scores from the initial condition of only 51.11%, rising to 71.29% in cycle I, and reaching 78.52% in cycle II. Furthermore, the students' classical completeness also improved significantly in each cycle, with all students in cycle II achieving completeness according to the Minimum Mastery Criteria (KKM) of 60. The application of this model also enhanced students' activeness and involvement in the learning process through group discussions and practicum activities. Based on these results, it can be concluded that the Problem Based Learning model is effective in improving learning outcomes of the science force concept for fourth-grade students at SD Kristen Patti.